Book Reviews - Judy Halden-Sullivan; Elizabeth French; Brad Lucas; Candace Walworth; Caleb Corkery (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Judy Halden-Sullivan - Embracing the "Beginner's Mind" Elizabeth French - Richardson, Scott. eleMENtary School—(Hyper) Masculinity in a Feminized Context. Rotterdam: Sense Publishers, 2012. Print. Brad Lucas - Ryden, Wendy and Ian Marshall. Reading, Writing, and the Rhetorics of Whiteness. NY: Routledge, 2012. Print. Candace Walworth - Kroll, Barry. The Open Hand: Arguing as an Art of Peace. Logan, UT: Utah State UP, 2013. Print. Caleb Corkery - Conway, Jeremiah. The Alchemy of Teaching: The Transformation of Lives. Boulder, CO: Sentient Publications, 2013. Print.